Aspergillus niger as a cell factory for the production of pyomelanin, a molecule with UV-C radiation shielding activity - Koch, Stella Marie; Freidank-Pohl, Carsten; Siontas, Oliver; Cortesao, Marta; Mota, Afonso; Runzheimer, Katharina; Jung, Sascha; Rebrosova, Katarina; Siler, Martin; Moeller, Ralf; Meyer, Vera (Frontiers in Microbiology, 2023)
Melanins are complex pigments with numerous biological functions that have potential applications in space exploration and biomedicine due to their radioprotective properties. Aspergillus niger, a fungus with naturally high radiation resistance, is well established as a biotechnologically harnessed cell factory, and is an eligible candidate for melanin production. In this study, we demonstrate that A. niger can produce fungal pyomelanin (PyoFun) via L-tyrosine inducible overproduction in a recombinant ΔhmgA mutant strain (OS4.3). PyoFun was characterized using three spectroscopic methods and its strong antioxidant properties were proven with a DPPH-assay. Additionally, the study evaluated the protective effect of PyoFun against non-ionizing radiation (monochromatic UV-C) and displayed a highly protective effect against radiation induced stress. PyoFun also demonstrated superior protection compared to the synthetically produced control pyomelanin (PyoSyn). These findings suggest that PyoFun has significant potential as a biological shield against harmful radiation. Particularly in space exploration settings, since the generated pyomelanin is synthesized extracellularly, unlike other known fungal melanins (L-DOPA-or DHN-melanin), there is no need for cell lysis for pigment purification, which makes it a valuable resource for biotechnology, biomedicine, and space industry. Further research is necessary to test its protective effect in a dried form and against ionizing radiation.